Photosynthesis : physiology and metabolism - Leegood, Richard C.; Sharkey, Thomas D., 1946-; Von Caemmerer, S. (Susanna) (Advances in photosynthesis, 2000)
The principal aim of Photosynthesis: Physiology and Metabolism is to provide final year undergraduates, graduate students and researchers with an up-to-date and comprehensive overview of photosynthetic carbon metabolism in plants, ranging from molecular to ecophysiological aspects. The book examines how CO2 is acquired by algae and by plants and is divided into three sections. The first section concentrates on the pathways (the Calvin-Benson-Bassham cycle and photorespiration, with particular emphasis on the enzyme ribulose bisphospate carboxylase/oxygenase, Rubisco) and the regulation of CO2 fixation. The second section deals with the fate of fixed carbon, in chapters on the synthesis of products, such as sucrose, starch, fructans and sugar alcohols, and with the regulation of cellular partitioning of carbon, including topics such as respiration and feedback regulation of photosynthesis by carbohydrates. The last section concentrates on the various problems that plants face in taking up CO2 from their environment, and how CO2 concentrating mechanisms operate in the algae and in plants with C4 photosynthesis and Crassulacean Acid Metabolism. The ecological significance of these mechanisms is also discussed.